Pertumbuhan Ekonomi dan Indeks Pembangunan Manusia di Provinsi Sulawesi Tengah - Bahasoan, Awal Nopriyanto; Khaldun, Riady Ibnu; Rahmat, Aswar; B Tahawa, Taufik Hidayat (Badan Riset dan Inovasi Daerah Sulawesi Tengah, 2019)
This study aims to determine the effect of economic growth on the human development index (HDI) in Central Sulawesi Province in 2015-2018. The type of this research is quantitative with the method of data analysis used in this study is panel data regression. The model combines cross-sectoral observations and time series data so that the number of observations increases degrees of freedom and reduces collinearity between explanatory variables and then improves the efficiency of econometric estimates. The effect of economic growth on HDI in Central Sulawesi Province shows a positive and significant relationship meaning that for every increase in economic growth of 1 percent, the HDI of Central Sulawesi Province will increase by 1.49.